In vitro wear of a zirconium-reinforced lithium silicate ceramic against different restorative materials - Alves, Larissa Marcia Martins [UNESP] (2019)
It is important to predict the wear behavior of a material as well as its potential to wear antagonized restorative materials. Thus, this study investigated the performance of zirconia-reinforced lithium silicate (ZLS) after wear with different antagonists. Thirty discs of ZLS were made and divided into three groups according to the antagonist (n = 10). Ten cylinders of each antagonist were also made. The parameters for the simulation of wear were: 30N, horizontal movement of 6 mm, and 1.7 Hz, totaling 300,000 cycles, in distilled water. Wear measurements (volume losses (mm3)) on the ZLS and antagonists were performed by digital optical profilometry or an analytical balance. Hardness of all materials was also measured, whereas roughness and Scanning Electron Microscopy (SEM) were only accessed for the ZLS. The wear and hardness values were subjected to one-way ANOVA and the Tukey Test (95%), while the roughness data was analyzed with paired T-test (95%). The hardness means of all materials were statistically different (zirconia > steatite = ZLS > acrylic resin) (p = 0.0001). Zirconia and steatite severely worn ZLS and only acrylic resin worn surfaces could be measured for roughness, which was significantly higher after wear (p = 0.007). SEM showed the ZLS's wear tracks when worn by steatite and zirconia. It was possible to observe differences of ZLS wear patterns depending on the antagonist and quantify the volumes worn with steatite (17.61 ± 2.65) and zirconia (41.98 ± 19.45), which were significantly different (p = 0.001). Acrylic resin promoted a superficial wear on ZLS that could not be quantified. In terms of the antagonists' materials, zirconia presented significantly different less volume loss compared to acrylic resin and steatite (p = 0.000). It can be concluded that zirconia caused more wear on ZLS than steatite and acrylic resin.